Steel plates for hot stamping and hot stamping parts

A surface treatment film with carbon black and Zr oxide on steel plates enhances heating efficiency and appearance, addressing productivity and weldability issues in hot stamping methods.

JP7620242B2Active Publication Date: 2025-01-23NIPPON STEEL CORPORATION

Patent Information

Application Number
JP2023512606
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-08
Publication Date
2025-01-23
Estimated Expiration
2041-04-08

AI Technical Summary

Technical Problem

Existing hot stamping methods for steel plates face challenges in productivity improvement, appearance quality, and spot weldability due to the need for lengthy heating times and the degradation of organic substances at high temperatures.

Method used

A surface treatment film with an emissivity of 60% or more at a wavelength of 8.0 μm is applied to steel plates, composed of carbon black and Zr oxide, with specific ratios and contents of carbon black and metal oxides, enhancing the heating rate and maintaining film integrity.

Benefits of technology

The solution significantly improves the productivity of hot-stamped parts by increasing the heating rate, ensures excellent appearance, and enhances spot weldability, while maintaining paint adhesion and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620242000001
    Figure 0007620242000001
  • Figure 0007620242000002
    Figure 0007620242000002
  • Figure 0007620242000003
    Figure 0007620242000003
Patent Text Reader

Abstract

This steel sheet for hot stamping has, on the entirety of at least one surface of the steel sheet, a surface treatment coating film demonstrating an emissivity of 60% or more at a wavelength of 8.0 µm at 25°C. The surface treatment coating film contains carbon black and at least one oxide selected from the group consisting of Zr oxide, Zn oxide and Ti oxide. The carbon black and the oxide are dispersed throughout the entirety of the surface treatment coating film. The surface treatment coating film has a silica content of 0-0.3 g / m2. When the adhesion amounts of the carbon black and the oxide are XCB (g / m2) and XOxide (g / m2), respectively, the following formulas are satisfied. 118.9≦24280/{6700/(100+76×XCB)+18000/(130+65×XOxide)}≦332.0
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel sheet for hot stamping and a hot stamped member. [Background technology]

[0002] In recent years, there has been an increasing demand to reduce the consumption of chemical fuels in order to protect the environment and prevent global warming, and this demand is affecting various manufacturing industries. For example, automobiles, which are indispensable as a means of transportation in daily life and activities, are no exception, and there is a demand for improving fuel efficiency by reducing the weight of the vehicle body. However, in the case of automobiles, simply reducing the weight of the body may lead to a decrease in safety, and this is not acceptable in terms of product quality. Therefore, when reducing the weight of the body, it is necessary to ensure appropriate safety.

[0003] Many of the structures of automobiles are formed from iron, particularly steel plates, and reducing the weight of the steel plates is important for reducing the weight of the vehicle body. Such demands for steel plates are not limited to the automobile manufacturing industry, but are also made in various manufacturing industries. In order to meet such demands, it is possible to simply reduce the weight of the steel plates by reducing the thickness of the steel plates. However, reducing the thickness of the steel plates leads to a decrease in the strength of the structures. For this reason, in recent years, research and development has been conducted on steel plates that can maintain or increase the mechanical strength of structures made of the steel plates by increasing the mechanical strength of the steel plates, even if they are thinner than steel plates that were previously used.

[0004] Generally, materials with high mechanical strength tend to have poor shape fixability during forming such as bending. Therefore, when processing into a complex shape, the processing itself becomes difficult. One of the means for solving the problem of formability is the so-called "hot stamping method (also called hot pressing method, hot pressing method, high temperature pressing method, die quenching method)". In this hot stamping method, the material to be formed is heated to a high temperature to transform (austenitize) into a structure called austenite, and the steel plate softened by heating is pressed to form, and cooled after forming. According to this hot stamping method, the material is once heated to a high temperature to soften it, so that the material can be easily pressed. Furthermore, the mechanical strength of the material can be increased by the quenching effect caused by cooling after forming. Therefore, this hot stamping method can obtain a formed product with good shape fixability and high mechanical strength.

[0005] For example, the following Patent Document 1 discloses a technique for manufacturing a molded product that can be used as an automobile part by processing a galvannealed steel sheet by a hot stamping method. Also, the following Patent Documents 2 and 3 disclose a technique for shortening the time required for heating to a desired temperature by providing an upper layer of an aluminum-plated steel sheet with a coating mainly made of an organic substance such as a carbon pigment. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2003-126921 A [Patent Document 2] JP 2011-149084 A [Patent Document 3] Special Publication No. 2017-518438 Summary of the Invention [Problem to be solved by the invention]

[0007] Here, the hot stamping method described in Patent Document 1 requires heating the steel sheet to be processed to the Ac3 point or higher, so that time must be secured for heating the steel sheet to the desired temperature, leaving room for improvement in productivity. Also, in the methods described in Patent Documents 2 and 3, the carbon pigments and the like contained in the coating are both organic substances, and therefore disappear at high temperatures of 750°C or higher, leaving room for improvement in productivity.

[0008] Therefore, the present invention has been made in consideration of the above problems, and an object of the present invention is to provide a steel sheet for hot stamping and a hot stamped member which are capable of further improving the productivity of hot stamped members, and which have excellent appearance and spot weldability. [Means for solving the problem]

[0009] In order to solve the above problems, the present inventors have conducted extensive research and have come to the conclusion that if the heating rate can be increased when a steel sheet is heated to a desired temperature of Ac3 point or higher, the heating time can be shortened, which can contribute to improving productivity. In addition, the present inventors have come to the conclusion that a hot stamping steel sheet having excellent appearance and excellent spot weldability can be obtained. The gist of the present invention, which was completed based on these findings, is as follows.

[0010] [1] A surface treatment film having an emissivity of 60% or more at 25°C at a wavelength of 8.0 μm is provided on at least one entire surface of the steel sheet, the surface treatment film being composed of carbon black and Zr oxide. , and and one or more oxides selected from the group consisting of Ti oxides, and the carbon black and the oxides are present in a dispersed state throughout the surface treatment film, and the surface treatment film has a silica content of 0 to 0.3 g / m 2 The amount of the carbon black and the amount of the oxide are each X CB (g / m 2 ), X Oxide (g / m 2 ) a steel sheet for hot stamping, which satisfies the following formula (1): 118.9≦24280 / {6700 / (100+76×X CB )+18000 / (130+65×X Oxide )}≦332.0 ··· Formula (1) [2] The steel sheet for hot stamping according to [1], wherein the surface treatment film contains 5.0 to 40.0 vol. % of the carbon black and 1.0 to 30.0 vol. % of the oxide. [3] The amount of carbon black attached X CB (g / m 2 ) and the amount of oxide attached X Oxide (g / m 2 ) and the ratio X Oxide / X CB The steel sheet for hot stamping according to [1] or [2], wherein R is 0.20 or more and 200.00 or less. [4] The amount of carbon black attached X CB is 0.030g / m 2 The amount of oxide adhesion X Oxide is 0.030g / m 2 The steel sheet for hot stamping according to any one of [1] to [3] above. [5] The steel sheet for hot stamping according to any one of [1] to [4], wherein the emissivity of the surface treatment film at 700° C. at a wavelength of 8.0 μm is 60% or more. [6] The steel sheet for hot stamping according to any one of [1] to [5], wherein one or both sides of the steel sheet for hot stamping have a metal plating layer between a substrate of the steel sheet and the surface treatment film. [7] A surface treatment film is provided on at least one entire surface of the steel sheet, the surface treatment film being Zr oxide. , and and one or more oxides selected from the group consisting of Ti oxides, and the amount of the oxide deposited is X Oxide is 0.030g / m 2 or more, and the surface treatment film has a silica content of 0 to 0.3 g / m 2 A hot stamped component. Effect of the Invention

[0011] INDUSTRIAL APPLICABILITY As described above, according to the present invention, it is possible to further improve the productivity of hot stamped members, and a steel sheet for hot stamping having excellent appearance and spot weldability can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Preferred embodiments of the present invention will be described in detail below.

[0013] (Steel sheets for hot stamping) The hot stamping steel sheet according to the embodiment of the present invention described below is capable of increasing the temperature rise rate when the steel sheet is heated in manufacturing a hot stamped member, thereby improving the productivity of the hot stamped member and further improving the appearance and spot weldability. The hot stamping steel sheet has a surface treatment film having an emissivity of 60% or more at a wavelength of 8.0 μm at 25° C. on the entire surface of at least one of the surfaces of the steel sheet. In this embodiment, by providing the surface treatment film on the entire surface of at least one of the surfaces of the steel sheet as described above, the emissivity at a wavelength of 8.0 μm at 25° C. can be increased to 60% or more, and the temperature rise rate when the steel sheet is heated can be increased.

[0014] In the hot stamping steel sheet according to the present embodiment, the type of the steel sheet (base steel sheet) serving as the base material is not particularly limited. Examples of such steel sheets include various hot-rolled steel sheets, cold-rolled steel sheets, and plated steel sheets. Plated steel sheets include steel sheets that have been subjected to, for example, hot-dip aluminum plating, hot-dip galvanizing, alloyed hot-dip galvanizing, and electrolytic galvanization, but are not limited to these plated steel sheets as long as they are applicable to hot stamping.

[0015] Conventionally, most of the steel sheets used for automotive frame parts and the like have been hot-rolled steel sheets, cold-rolled steel sheets, or plated steel sheets coated with aluminum, zinc, etc. These steel sheets have low emissivity, so the heating rate in response to radiant heating with a wavelength of around 8.0 μm is low.

[0016] In this embodiment, a specific surface treatment film is applied to the entire surface of at least one surface of a steel sheet, thereby increasing the heating rate during hot stamp heating. By hot stamping the heated steel sheet, it is possible to quickly quench the entire surface of the steel sheet to form a quenched structure (martensite structure).

[0017] In this embodiment, a surface treatment film having a high emissivity is applied to the entire surface of at least one surface of the steel sheet. Specific methods for applying the surface treatment film include painting and lamination, but are not limited to these methods. The above-mentioned surface treatment film may be applied to only one surface of the steel sheet, or may be applied to both surfaces of the steel sheet. The emissivity of the region to which the surface treatment film is applied at a wavelength of 8.0 μm at 25° C. is 60% or more. The emissivity of the region to which the surface treatment film is applied at a wavelength of 8.0 μm at 25° C. is preferably 70% or more, and more preferably 80% or more.

[0018] The emissivity can be measured according to the method described in the Japanese Industrial Standard JIS R 1801 (2002). In this case, a sample is placed in a Fourier transform infrared spectrophotometer, and the radiation intensity at a wavelength of 8.0 μm is measured at 25° C. to calculate the emissivity.

[0019] It is also possible to measure the radiation intensity of a target area at 25°C using a radiation thermometer set to a measurement wavelength of 8.0 µm, and calculate the emissivity from the ratio to the radiation intensity of a black body.

[0020] When applying a surface treatment film to the entire surface of a steel sheet by painting, for example, an organic or inorganic treatment liquid containing carbon black and a metal oxide can be applied to the entire surface of the steel sheet by using a roll coater, curtain coater or inkjet, and then the volatile components in the treatment liquid are dried, thereby applying the surface treatment film.

[0021] In particular, when applying paint by inkjet, it is possible to continuously change the film thickness.

[0022] <Surface treatment film> In the hot stamping steel sheet according to this embodiment, the emissivity at 25°C at a wavelength of 8.0 μm of the surface on which the surface treatment film is applied is 60% or more. If the emissivity at 25°C at a wavelength of 8.0 μm is less than 60%, it becomes difficult to efficiently use radiant heating, and the temperature rise rate cannot be increased. The emissivity at 25°C at a wavelength of 8.0 μm is preferably 80% or more. By making the emissivity at 25°C at a wavelength of 8.0 μm 80% or more, it becomes possible to use radiant heating more efficiently, and the temperature rise rate can be further increased. Note that the higher the emissivity at 25°C at a wavelength of 8.0 μm of the surface on which the surface treatment film is applied, the better, and the upper limit is not specified, and it may be 100%.

[0023] In order to achieve an emissivity of 60% or more at a wavelength of 8.0 μm at 25° C., the surface treatment film according to this embodiment contains carbon black and a specific metal oxide as described in detail below. The surface treatment film according to this embodiment may further contain a binder component and various additives, etc., as necessary. Furthermore, the surface treatment film according to this embodiment may not contain silica, or may contain silica within a certain range. By adjusting the contents of carbon black and metal oxide, etc., and the film thickness of the surface treatment film, it is possible to achieve a desired emissivity.

[0024] More specifically, the surface treatment film according to this embodiment contains carbon black and one or more oxides selected from the group consisting of Zr oxide, Zn oxide, and Ti oxide, and the carbon black and the oxides are dispersed throughout the surface treatment film. CB (g / m 2 ) and the amount of oxide attached is expressed as X Oxide (g / m 2 ), the surface treatment film according to this embodiment satisfies the relationship represented by the following formula (1).

[0025] 118.9≦24280 / {6700 / (100+76×X CB )+18000 / (130+65×X Oxide )}≦332.0 ··· Formula (1)

[0026] The above formula (1) defines the relationship between the rate of increase (%) of temperature rise (°C / s) and the amount of carbon black and oxides attached. More specifically, this formula stipulates that, with respect to the rate of increase of temperature rise, carbon black functions as a heat absorbing material in the range up to 700°C, and Zr oxide, Zn oxide, and Ti oxide remaining in this temperature range function as heat absorbing materials in the range of 700°C or higher.

[0027] As briefly mentioned above, the surface treatment film according to this embodiment can be formed by applying a treatment liquid containing carbon black and a specific oxide to the surface of a steel sheet. As a result, in the surface treatment film according to this embodiment, the carbon black and the oxide are dispersed throughout the surface treatment film. By dispersing the carbon black and the oxide throughout the surface treatment film, the emissivity of the surface treatment film at a wavelength of 8.0 μm at 25° C. can be made uniform throughout the film. As a result, when the hot stamping steel sheet according to this embodiment is heated, the entire surface treatment film can be heated quickly and uniformly.

[0028] The distribution state of the carbon black and the oxides can be confirmed by area analysis of the surface treatment film with an electron probe micro analyzer (EPMA) for elements derived from the carbon black (e.g., C) and elements derived from the oxides (i.e., Zr, Zn, Ti).

[0029] In addition, when a laminated film is formed by separately preparing a treatment liquid containing carbon black and a treatment liquid containing an oxide and separately applying these treatment liquids, the carbon black and the oxide do not exist in a dispersed state throughout the film. Furthermore, when attempting to form a film using a plurality of treatment liquids in this manner, a second layer of film must be formed after the first layer is formed, which increases the size of the production equipment and the production costs.

[0030] In addition, the surface treatment film according to this embodiment has a carbon black adhesion amount X CB and the amount of oxide adhesion X Oxide By satisfying the relationship represented by the above formula (1), the emissivity at 25°C at a wavelength of 8.0 μm becomes 60% or more, and the degree of increase in the temperature rise rate becomes significant. If the value specified in the middle term of the above formula (1) is less than 118.9, the amount of carbon black and oxide attached is insufficient, and the above-mentioned emissivity cannot be realized. The value specified in the middle term of the above formula (1) is preferably 119.0 or more, more preferably 170.0 or more, and even more preferably 220.0 or more. On the other hand, if the value specified in the middle term of the above formula (1) exceeds 332.0, the adhesion of the coating decreases, which is not preferable. The value specified in the middle term of the above formula (1) is preferably 330.0 or less, more preferably 310.0 or less, and even more preferably 300.0 or less.

[0031] Here, the amount of carbon black attached to the surface treatment film is X CB can be measured by cross-sectional analysis of the surface treatment film using a transmission electron microscope (TEM) as follows. That is, a region represented by film thickness x 5 μm is cross-sectionally analyzed by TEM-EDS analysis to measure the film thickness of the surface treatment film and the area ratio occupied by particles with a carbon content of 70 mass % or more. When the film thickness is d (μm) and the area ratio is a (%), the value represented by d x a is the amount of carbon black attached X CB (g / m 2)

[0032] In addition, the amount of oxide of at least one of Zr, Zn, and Ti in the surface treatment film is X Oxide means the amount of Zr oxide, Zn oxide, and Ti oxide (i.e., ZrO2, ZnO, and TiO2) adhering per unit area as metal Zr, metal Zn, and metal Ti. The amount of these oxides adhering, X Oxide can be determined by performing elemental analysis on the surface of the surface treatment film using an X-ray fluorescence analyzer (ZSX Primus, manufactured by RIGAKU Corporation) and quantifying the amounts of metallic Zr, metallic Zn, and metallic Ti.

[0033] The steel sheet for hot stamping according to this embodiment has the above-mentioned characteristics, and therefore can achieve an emissivity of 60% or more at a wavelength of 8.0 μm at 700° C. Below, the substances contained in the surface treatment film, which are characteristic for achieving the above-mentioned emissivity, will be described in more detail.

[0034] Carbon black On the surface of the steel sheet on the side to which the surface treatment film is applied, the amount of carbon black attached to the surface treatment film is X CB is 0.030g / m 2 It is preferable that the amount of adhesion is equal to or more than X. CB 0.030g / m 2 By setting the temperature to 700° C. or more, it is possible to reliably increase the temperature rise rate in the range up to 700° C. CB is more preferably 0.100 g / m 2 On the other hand, the adhesion amount X CB The upper limit of the adhesion amount X is determined by the above formula (1). CB is preferably 0.800 g / m 2 or less, more preferably 0.600 g / m 2 The following is the result.

[0035] Moreover, the surface treatment film more preferably contains 5.0 to 40.0% by volume of carbon black. Carbon black has the effect of increasing the temperature rise rate, particularly in the range up to 700°C. The thickness of the surface treatment film may vary locally due to the roughness or waviness of the steel sheet, or the difference in the rate at which volatile components such as water in the treatment solution evaporate during film formation. In this case, by having the carbon black content of 5.0% by volume or more, the difference between the part that appears black due to carbon black and the other parts can be suppressed, and the design can be maintained, which is preferable in terms of appearance. On the other hand, by having the carbon black content in the surface treatment film of 40.0% by volume or less, the decrease in paint adhesion after hot stamp heating can be suppressed. Although the mechanism is not clear, it is presumed that the inhibition of the binding between the paint and the substrate is suppressed by suppressing the remaining carbon black or compounds derived from the oxides of carbon black.

[0036] In addition, since the main components of carbon black are carbon, hydrogen, and oxygen, carbon black disappears when heated to high temperatures. Therefore, by including carbon black in the surface treatment film, it is possible to maintain performance after hot stamping, such as adhesion after painting.

[0037] By the carbon black content being 5.0% by volume or more, oxidation of the steel sheet or plating layer located under the surface treatment film is suppressed, so that reactivity is ensured when a paint (treatment agent) is applied, strong bonding is achieved, and paint adhesion is maintained. In addition, the emissivity can be increased, and the temperature rise rate can be increased. The carbon black content in the surface treatment film is more preferably 8.0% by volume or more. By making the carbon black content in the surface treatment film 8.0% by volume or more, it is possible to further increase the temperature rise rate. On the other hand, by making the carbon black content in the surface treatment film 40.0% by volume or less, it is possible to suppress an increase in the coating cost while sufficiently obtaining the effect of increasing the emissivity. The carbon black content in the surface treatment film is more preferably 30.0% by volume or less. By making the carbon black content in the surface treatment film 30.0% by volume or less, it is possible to further suppress the coating cost.

[0038] <Metal oxide> On the surface of the steel sheet on the side to which the surface treatment film is applied, the total amount of Zr oxide, Zn oxide, and Ti oxide in the surface treatment film is X Oxide is 0.030g / m 2 It is preferable that the amount of adhesion is equal to or more than X. Oxide 0.030g / m 2 By setting the temperature to 700° C. or higher, it is possible to reliably increase the rate of temperature rise in the range of 700° C. or higher. Oxide is more preferably 0.060 g / m 2 On the other hand, the adhesion amount X O xide The upper limit of the adhesion amount X is determined by the above formula (1). Oxide is preferably 0.500 g / m 2 More preferably, it is 0.300 g / m or less. 2 The following is the result.

[0039] Moreover, the surface treatment film more preferably contains Zr oxide, Zn oxide, and Ti oxide in a total amount of 1.0 to 30.0% by volume. The oxides of these elements (i.e., metal oxides of Zr, Zn, and Ti) remain in the surface treatment film even when heated to a high temperature of 700°C or higher where the effect of carbon black is reduced. As a result, in the portion to which the surface treatment film is applied, these metal oxides have a higher emissivity than the steel sheet surface or the plated surface at a high temperature of 700°C or higher, so that the amount of heat input by radiant heat from the heating atmosphere is increased. This makes it possible to maintain the effect of increasing the temperature rise rate even at a high temperature of 700°C or higher. By making the content of these metal oxides 1.0% by volume or more, the effect of increasing the temperature rise rate can be sufficiently obtained. The content of these metal oxides is more preferably 3.0% by volume or more. On the other hand, by making the content of these metal oxides 30.0% by volume or less, the film cost can be suppressed, which is economically preferable. The content of these metal oxides is more preferably 25.0% by volume or less.

[0040] The content (volume %) of various compounds such as carbon black and metal oxides in the surface treatment film can be calculated from the area percentage of the cross section by embedding the sample in resin, polishing it, and observing the cross section with a scanning electron microscope (SEM). The compounds can also be estimated by quantitative analysis using the EDX function attached to the SEM.

[0041] In the surface treatment film according to this embodiment, the adhesion amount X of the carbon black is CB (g / m 2 ) and the amount of oxide attached X Oxide (g / m 2 ) and the ratio X Oxide / X CB The ratio X is preferably 0.20 or more and 200.00 or less. Oxide / X CB By keeping the ratio X within the above range, it is possible to more appropriately heat the area to which the surface treatment film is applied. Oxide / X CBis more preferably 0.40 to 10.00, and further preferably 0.60 to 5.00.

[0042] Furthermore, the surface treatment film according to this embodiment may contain various binder components and additives in addition to the carbon black and metal oxides described above.

[0043] <Binder components> The binder component that can be contained in the surface treatment film according to this embodiment is preferably a water-dispersible or water-soluble resin. The content of the binder component selected from water-dispersible or water-soluble resins is preferably 40 volume % or more relative to the total volume of the surface treatment film.

[0044] As the binder component selected from water-dispersible or water-soluble resins, various known resins exhibiting water dispersibility or water solubility can be used. Examples of such resins exhibiting water dispersibility or water solubility include polyurethane resins, polyester resins, acrylic resins, epoxy resins, fluororesins, polyamide resins, polyolefin resins, and polymer compounds obtained by hydrolysis and condensation polymerization of silane coupling agents. It is more preferable that the binder component is one or more selected from the group consisting of polyester resins, polyurethane resins, polyolefin resins, acrylic resins, epoxy resins, fluororesins, and polyamide resins. In addition, when multiple resins are used as the binder component, the total content of the multiple resins used is treated as the content of the binder component.

[0045] In addition, when a polyurethane resin is used as the binder component, the polyurethane resin is preferably a polyether-based polyurethane resin, because the use of a polyether-based polyurethane resin can prevent the occurrence of hydrolysis caused by acid or alkali, compared with a polyester-based polyurethane resin, and because the use of a polyether-based polyurethane resin can suppress the formation of a hard and brittle film, compared with a polycarbonate-based polyurethane resin, thereby ensuring adhesion during processing and corrosion resistance of the processed part.

[0046] Whether or not polyurethane resin is contained can be determined by detecting the 3330 cm -1 (NH telescopic), 1730cm -1 (C=O expansion and contraction), 1530cm -1 (CN), 1250cm -1 It can be judged based on whether the characteristic absorption of (CO) is observed. In addition, the polyurethane resin content can also be determined from the obtained characteristic absorption intensity by creating a calibration curve showing the relationship between the content and the characteristic absorption intensity using a sample with a known content.

[0047] In addition, for resins other than the above polyurethane resins, it is possible to determine the presence or absence and the amount of content in the same manner as for the above polyurethane resins, by paying attention to the characteristic absorption derived from the functional groups specific to each resin.

[0048] Additives In the surface treatment film according to this embodiment, various additives such as a leveling agent, a water-soluble solvent, a metal stabilizer, an etching inhibitor, etc. can be contained as additives used in preparing the treatment liquid prior to film formation, within a range that does not impair the effects of the present invention.

[0049] The leveling agent may be a nonionic or cationic surfactant, such as a polyethylene oxide or polypropylene oxide adduct, or an acetylene glycol compound.

[0050] Examples of the water-soluble solvent include alcohols such as ethanol, isopropyl alcohol, t-butyl alcohol, and propylene glycol; cellosolves such as ethylene glycol monobutyl ether and ethylene glycol monoethyl ether; esters such as ethyl acetate and butyl acetate; and ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone.

[0051] Examples of metal stabilizers include chelating compounds such as EDTA (ethylenediaminetetraacetic acid) and DTPA (diethylenetriaminepentaacetic acid).

[0052] Etch inhibitors include, for example, amine compounds such as ethylenediamine, triethylenepentamine, guanidine, and pyrimidine.

[0053] The contents of the binder components and additives can be measured in the same manner as in the case of carbon black and metal oxides.

[0054] <Silica> As mentioned above, the surface treatment film according to this embodiment may not contain silica, or may contain silica within a certain range. More specifically, the silica content in the surface treatment film according to this embodiment is 0 to 0.3 g / m 2 Silica is 0.3g / m 2 If the content exceeds 0.3 g / m, the temperature increase effect cannot be expected and the cost becomes high, which is not economically preferable. In addition, since silica is a substance with low electrical conductivity, the content of silica is less than 0.3 g / m 2 If the content exceeds 100%, it is not preferable in terms of weldability after hot stamping. When silica is contained, the smaller the silica content of the surface treatment film, the better. The silica content of the surface treatment film is more preferably 0.10 g / m 2 More preferably, it is 0.05 g / m or less. 2 The following is the result.

[0055] <Thickness of surface treatment film> The thickness of the surface treatment film containing the above components is preferably, for example, 0.5 to 5.0 μm. By setting the thickness of the surface treatment film within the above range, the emissivity at a wavelength of 8.0 μm at 25° C. can be more reliably set to 60% or more. The thickness of the surface treatment film is more preferably 1.0 to 3.0 μm.

[0056] <Metal plating layer> The hot stamping steel sheet according to the present embodiment preferably has a metal plating layer at least partially between the base steel sheet and the surface treatment film on one or both sides of the hot stamping steel sheet. By having the metal plating layer, the corrosion resistance after painting after hot stamping can be further improved. In addition, the presence of the metal plating layer can prevent iron scale from being generated by heating during hot stamping. Iron scale contaminates the heating furnace and adheres to rolls used for transportation, which is a burden in manufacturing. Therefore, when iron scale is generated, a process such as shot blasting is required to remove the iron scale, which is not economically preferable.

[0057] The type of the metal plating layer is not particularly limited. Examples of metal plating constituting the metal plating layer include aluminum plating, Al-Si plating, zinc plating, alloyed zinc plating, Zn-Ni plating, Zn-Al-Mg plating, and Zn-Al-Mg-Si plating.

[0058] The method for forming the metal plating layer includes, but is not limited to, hot-dip plating, electroplating, physical vapor deposition, chemical vapor deposition, and the like.

[0059] <Base material steel plate> Next, the base steel sheet of the hot stamping steel sheet according to the present embodiment is not particularly limited as long as it is a steel sheet suitable for use in the hot stamping process. As a steel sheet applicable to the hot stamping steel sheet according to the present embodiment, for example, a steel sheet containing, in mass%, C: 0.10 to 0.40%, Si: 0.01 to 0.60%, Mn: 0.50 to 3.00%, P: 0.05% or less, S: 0.020% or less, Al: 0.10% or less, Ti: 0.01 to 0.10%, B: 0.0001 to 0.0100%, N: 0.010% or less, with the balance being Fe and impurities, can be exemplified. In addition, as the form of the base steel sheet, for example, a steel sheet such as a hot rolled steel sheet or a cold rolled steel sheet can be exemplified. Hereinafter, the chemical components of the base steel sheet will be described in detail. In the following description of the chemical components of the base steel plate, the notation "%" means "mass %" unless otherwise specified.

[0060] [C: 0.10~0.40%] C is contained to ensure the desired mechanical strength. When the C content is 0.10% or more, a sufficient improvement in mechanical strength is obtained, and the effect of containing C is fully obtained. Therefore, the C content is preferably 0.10% or more. The C content is more preferably 0.20% or more. On the other hand, when the C content is 0.40% or less, the strength of the steel sheet can be hardened and improved while the decrease in elongation and reduction of area can be suppressed. Therefore, the C content is preferably 0.40% or less. The C content is more preferably 0.35% or less.

[0061] [Si: 0.01~0.60%] Si is one of the strength-improving elements that improve mechanical strength, and is contained in order to secure the desired mechanical strength, similar to C. When the Si content is 0.01% or more, the strength-improving effect is fully exerted, and sufficient improvement in mechanical strength is obtained. Therefore, the Si content is preferably 0.01% or more. The Si content is more preferably 0.10% or more. On the other hand, since Si is also an easily oxidizable element, when the Si content is 0.60% or less, the decrease in wettability during hot-dip Al plating due to the influence of Si oxide formed on the steel sheet surface layer is suppressed, and the occurrence of bare spots can be suppressed. Therefore, the Si content is preferably 0.60% or less. The Si content is more preferably 0.40% or less.

[0062] [Mn: 0.50~3.00%] Mn is one of the strengthening elements that strengthen steel, and is also one of the elements that enhance hardenability. Furthermore, Mn is an element that is effective in preventing hot embrittlement caused by S, which is one of the impurities. When the Mn content is 0.50% or more, these effects can be sufficiently obtained. Therefore, in order to reliably exhibit the above effects, the Mn content is preferably 0.50% or more. The Mn content is more preferably 0.80% or more. On the other hand, since Mn is an austenite forming element, when the Mn content is 3.00% or less, the amount of retained austenite phase does not become too large, and a decrease in strength is suppressed. Therefore, the Mn content is preferably 3.00% or less. The Mn content is more preferably 1.50% or less.

[0063] [P:0.05% or less] P is an impurity contained in steel. By making the P content 0.05% or less, it is possible to suppress the P contained in the steel sheet from segregating at the grain boundaries of the steel sheet and reducing the toughness of the base material of the hot stamped body, and to suppress the reduction in the delayed fracture resistance of the steel sheet. Therefore, the P content is preferably 0.05% or less, and it is preferable to make the P content as small as possible.

[0064] [S:0.020% or less] S is an impurity contained in steel. By making the S content 0.020% or less, it is possible to suppress the S contained in the steel sheet from forming sulfides that reduce the toughness of the steel sheet, and to suppress a decrease in the delayed fracture resistance of the steel sheet. Therefore, the S content is preferably 0.020% or less, and it is preferable to make the S content as small as possible.

[0065] [Al: 0.10% or less] Al is generally used for the purpose of deoxidizing steel. On the other hand, by making the Al content 0.10% or less, the increase in Ac3 point of the steel sheet is suppressed, so that the heating temperature required to ensure the hardenability of the steel during hot stamping can be reduced, which is desirable for hot stamping production. Therefore, the Al content of the steel sheet is preferably 0.10% or less, more preferably 0.05% or less, and further preferably 0.01% or less.

[0066] [Ti: 0.01~0.10%] Ti is one of the strength enhancing elements. When the Ti content is 0.01% or more, the strength improving effect and the oxidation resistance improving effect can be sufficiently obtained. Therefore, in order to reliably realize the above effects, the Ti content is preferably 0.01% or more. The Ti content is more preferably 0.03% or more. On the other hand, when the Ti content is 0.10% or less, for example, the formation of carbides and nitrides is suppressed, the softening of the steel can be suppressed, and the desired mechanical strength can be sufficiently obtained. Therefore, the Ti content is preferably 0.10% or less. The Ti content is more preferably 0.08% or less.

[0067] [B:0.0001~0.0100%] B acts during quenching to improve strength. When the B content is 0.0001% or less, such a strength improving effect can be sufficiently obtained. Therefore, the B content is preferably 0.0001% or more. The B content is more preferably 0.0010% or more. On the other hand, when the B content is 0.0100% or less, the formation of inclusions is reduced, embrittlement of the steel sheet is suppressed, and a decrease in fatigue strength can be suppressed. Therefore, the B content is preferably 0.0100% or less. The B content is more preferably 0.0040% or less.

[0068] [N:0.010% or less] N is an impurity contained in steel. By making the N content 0.010% or less, the formation of nitrides due to N contained in the steel plate is suppressed, and the deterioration of the toughness of the steel plate can be suppressed. Furthermore, when B is contained in the steel plate, the N contained in the steel plate is suppressed from combining with B to reduce the amount of solid-solubilized B, and the deterioration of the hardenability improving effect of B can be suppressed. Therefore, the N content is preferably 0.010% or less, and it is more preferable to make the N content as small as possible.

[0069] In addition, the base steel sheet of the hot stamping steel sheet according to this embodiment may further contain elements such as Cr, Mo, Ni, Co, Cu, Mo, V, Nb, Sn, W, Ca, REM, O, and Sb as optional added elements.

[0070] [Cr:0~1.00%] Cr is an element that improves the hardenability of steel sheet. In order to fully obtain this effect, the Cr content is preferably 0.01% or more. On the other hand, by making the Cr content 1.00% or less, the effect can be fully obtained while suppressing an increase in costs. Therefore, when Cr is contained, the Cr content is preferably 1.00% or less.

[0071] [Ni:0~2.00%] [Co: 0-2.00%] Ni and Co are elements that improve the hardenability of steel and enable the strength of the steel plate member after hardening to be stably ensured. In order to fully exert such effects, the Ni content is preferably 0.10% or more, and the Co content is preferably 0.10% or more. On the other hand, by making the Ni content and the Co content each 2.00% or less, the above effects can be fully obtained while improving economic efficiency. Therefore, when contained, the Ni content is preferably 2.00% or less, and the Co content is preferably 2.00% or less.

[0072] [Cu:0~1.000%] Cu is an element that enhances the hardenability of steel and enables the strength of the steel plate member after hardening to be stably secured. Cu also improves pitting corrosion resistance in a corrosive environment. In order to fully exert such effects, it is preferable that the Cu content is 0.100% or more. On the other hand, by making the Cu content 1.000% or less, the above effects can be sufficiently obtained while improving economic efficiency. Therefore, when Cu is contained, it is preferable that the Cu content is 1.000% or less.

[0073] [Mo:0~1.00%] Mo is an element that enhances the hardenability of steel and enables the strength of the steel plate member after hardening to be stably ensured. In order to fully exert such effects, the Mo content is preferably 0.10% or more. On the other hand, by making the Mo content 1.00% or less, the above effects can be sufficiently obtained while improving economic efficiency. Therefore, when Mo is contained, the Mo content is preferably 1.00% or less.

[0074] [V:0~1.00%] V is an element that enhances the hardenability of steel and enables the strength of the steel plate member after hardening to be stably ensured. In order to fully exert such effects, it is preferable that the V content is 0.10% or more. On the other hand, by making the V content 1.00% or less, the above effects can be sufficiently obtained while improving economic efficiency. Therefore, when V is contained, it is preferable that the V content is 1.00% or less.

[0075] [Nb: 0-1.00%] Nb is an element that enhances the hardenability of steel and enables the strength of the steel plate member after hardening to be stably ensured. In order to fully exert such effects, the Nb content is preferably 0.01% or more. On the other hand, by making the Nb content 1.00% or less, the above effects can be sufficiently obtained while improving the economic efficiency. Therefore, when Nb is contained, the Nb content is preferably 1.00% or less.

[0076] [Sn: 0~1.00%] Sn is an element that improves pitting corrosion resistance in a corrosive environment. In order to fully exert this effect, the Sn content is preferably 0.01% or more. On the other hand, by making the Sn content 1.00% or less, the decrease in grain boundary strength is suppressed, and the decrease in toughness can be suppressed. Therefore, when Sn is contained, the Sn content is preferably 1.00% or less.

[0077] [W:0~1.00%] W is an element that enhances the hardenability of steel and enables the strength of the steel plate member after hardening to be stably secured. W also improves pitting corrosion resistance in a corrosive environment. In order to fully exert such effects, it is preferable that the W content is 0.01% or more. On the other hand, by making the W content 1.00% or less, the above effects can be sufficiently obtained while improving economic efficiency. Therefore, when W is contained, it is preferable that the W content is 1.00% or less.

[0078] [Ca: 0~0.010%] Ca is an element that has the effect of refining inclusions in steel and improving toughness and ductility after quenching. In order to fully exert such effects, the Ca content is preferably 0.001% or more, and more preferably 0.002% or more. On the other hand, by making the Ca content 0.010% or less, the effect can be sufficiently obtained while the cost can be suppressed. Therefore, when Ca is contained, the Ca content is preferably 0.010% or less, and more preferably 0.004% or less.

[0079] [REM:0~0.30%] Like Ca, REM is an element that has the effect of refining inclusions in steel and improving toughness and ductility after quenching. In order to fully exert such effects, the REM content is preferably 0.001% or more, and more preferably 0.002% or more. On the other hand, by making the REM content 0.30% or less, the effect can be sufficiently obtained while suppressing costs. Therefore, when REM is contained, the REM content is preferably 0.30% or less, and more preferably 0.20% or less.

[0080] Here, REM refers to Sc, Y and lanthanoids, a total of 17 elements, and the above REM content means the total content of these elements. REM is added to molten steel using, for example, an Fe-Si-REM alloy, which includes, for example, Ce, La, Nd, and Pr.

[0081] [O:0.0070% or less] O is not an essential element, and is contained in steel as an impurity, for example. O is an element that causes deterioration of the properties of steel sheets by forming oxides and becoming the starting point of fracture. In addition, oxides present in the vicinity of the surface of the steel sheet may cause surface defects and deteriorate the appearance quality. For this reason, the lower the O content, the better. In particular, by making the O content 0.0070% or less, deterioration of properties can be suppressed, so the O content is preferably 0.0070% or less. The lower limit of the O content is not particularly limited and may be 0%, but the practical lower limit of the O content in actual operation and refining is 0.0005%.

[0082] [Sb:0.100% or less] The lower limit of the Sb content is not particularly limited, and may be 0%. Sb is an effective element for improving the wettability and adhesion of plating. To obtain this effect, it is preferable to contain 0.001% or more of Sb. On the other hand, by keeping the Sb content at 0.100% or less, it is possible to suppress defects that occur during manufacturing and to suppress a decrease in toughness. Therefore, the Sb content is preferably 0.100% or less.

[0083] The balance other than the above components is Fe and impurities. The base steel sheet may also contain impurities that are mixed in during the manufacturing process, etc. Examples of such impurities include Zn (zinc).

[0084] An example of the chemical components of the base steel sheet of the hot stamping steel sheet according to this embodiment has been described in detail above.

[0085] The area of ​​the steel sheet having the above chemical composition and surface treatment film applied thereto can be made into a hot stamped component having a tensile strength of about 1000 MPa or more by heating and quenching using a hot stamping method. In addition, in the hot stamping method, press working can be performed in a softened state at high temperature, so that the material can be easily formed.

[0086] <Manufacturing of hot stamped parts> Various hot stamped members, such as automobile frame parts, can be produced using a steel sheet for hot stamping having the above-mentioned surface treatment film applied to the entire surface of at least one surface.

[0087] First, a surface treatment film is applied to the entire surface of at least one surface of a metal material such as a coiled steel sheet. Then, various processes such as cutting and punching by pressing are performed to obtain the hot stamping steel sheet according to this embodiment. Alternatively, the hot stamping steel sheet according to this embodiment can be obtained by applying a surface treatment film to a steel sheet that has been cut or punched by pressing. Furthermore, by changing the film thickness of the surface treatment film, the emissivity can be changed continuously.

[0088] For example, the hot stamping steel sheet to which the surface treatment film is applied as described above is hot stamped. Examples of the heating device include an electric heating furnace, a gas heating furnace, a far-infrared furnace, and a normal heating device equipped with an infrared heater. The surface on which the surface treatment film is applied to increase the emissivity has a high heating rate due to a large heat transfer effect by radiation, so the temperature is quickly raised to a temperature of the Ac3 point or higher at which the metal structure transforms into the austenite phase. As a result, in the manufacturing method of the hot stamped member according to this embodiment, the productivity of the hot stamped member can be further improved by shortening the heating time. In this embodiment, the specific heating conditions are not particularly limited, and it is sufficient to appropriately control the heating device to be used.

[0089] Next, the heated steel sheet is formed and cooled. The portion heated to or above the Ac3 point temperature at which the metal structure of the steel material transforms into the austenite phase is quenched to increase its strength. This allows for the production of a hot stamped part with improved strength due to quenching.

[0090] As mentioned above, by changing the thickness of the surface treatment film, the rate of temperature rise also changes continuously, and by utilizing this, it is possible to continuously change the hardness. In the area where the surface treatment film is thick, the rate of temperature rise is high, so austenitization progresses the most, and the strength increases due to the formation of martensite during quenching during cooling. On the other hand, in the area where the film is thin, the ratio of austenite phase during heating is low, and the amount of martensite formed is less than in the area where the film is thick, so the strength decreases.

[0091] <Hot stamping parts> The hot stamped member obtained in the above manner has a surface treatment film on the entire surface of at least one surface of the steel sheet. The surface treatment film contains one or more oxides selected from the group consisting of Zr oxide, Zn oxide, and Ti oxide, and has an oxide adhesion amount X Oxide is 0.030g / m 2 The surface treatment film has a silica content of 0 to 0.3 g / m 2 The carbon black present in the surface treatment film of the hot stamping steel sheet used as the material for the hot stamping component disappears through the hot stamping process, and the above metal oxides remain. The amount of oxide adhesion X present in the surface treatment film of the hot stamping component Oxide depends on the amount of oxide in the surface treatment film of the hot stamping steel sheet used as the base material, but the upper limit is approximately 0.600 g / m 2 It is. EXAMPLES

[0092] Examples of the present invention will be described below, but the conditions in the examples are merely examples of conditions adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to these examples. Various conditions may be adopted in the present invention as long as they do not deviate from the gist of the present invention and achieve the object of the present invention.

[0093] It is preferable to use a steel sheet having high mechanical strength (meaning various properties related to mechanical deformation and destruction such as tensile strength, yield point, elongation, reduction in area, hardness, impact value, fatigue strength, etc.) as the base steel sheet. The chemical composition of the base steel sheet before plating used in the hot stamping steel sheets shown in the following examples is shown in Table 1 below.

[0094] [Table 1]

[0095] A surface treatment film was applied to base steel sheets (steel Nos. S1 to S18) having the chemical compositions shown in Table 1. More specifically, for each base steel sheet, a steel sheet measuring 100 mm in width, 200 mm in length and 1.2 mm in thickness was prepared, and after plating with metal, a surface treatment film was applied to the entire surface of one or both sides of some of the steel sheets. For comparison, no surface treatment film was applied to some of the steel sheets.

[0096] In addition to the aqueous acrylic resin as a binder component, an aqueous treatment liquid containing at least one of commercially available carbon black and compounds such as TiO2, ZrO2, ZnO, Fe2O3, Fe3O4, CuO, SiO2, TiC, TiN, SiC, and SiN was applied to the surface of the base steel sheet using an industrial inkjet printer and dried to provide a surface treatment film. Some aqueous treatment liquids further contained silica in addition to the above components. In some verification examples, an aqueous treatment liquid containing carbon black and an aqueous treatment liquid containing metal oxide were prepared separately, and each treatment liquid was laminated. The thickness of the surface treatment film was within the range of 1.0 to 2.5 μm, and when applied to both sides, the same type of film was applied to both sides.

[0097] Then, a thermocouple was connected to the center of the steel sheet to which the surface treatment film was applied and the center of the steel sheet to which the surface treatment film was not applied, respectively, so that the temperature at each position could be measured. The steel sheet was then heated in an electric heating furnace set at a temperature of 920°C, and when the steel sheet to which the film was applied reached 880°C, the steel sheet was removed from the heating furnace. The steel sheet was rapidly cooled using a flat die to obtain a hot stamped part.

[0098] The radiation intensity at the center of the steel sheet to which the surface treatment film was applied was measured at 25° C. with a wavelength of 8.0 μm using a radiation thermometer, and the emissivity (%) was calculated from the ratio to the radiation intensity of a black body.

[0099] Note that some of the base steel sheets were plated with Al-10% Si by mass, Zn, Zn-11% Al-3% Mg-0.2% Si by mass, and Al by hot-dip plating, and Zn-3% Ni by electroplating, before being given the above-mentioned surface treatment film. In the case of the hot-dip plating method, the base steel sheet was immersed in a plating bath, and then the coating weight was reduced to 70 g / m per side by gas wiping. 2 In the case of electroplating, the coating weight on one side was adjusted to 20 g / m 2 was adjusted to.

[0100] The coating composition and temperature rise rate of the portion to which the surface treatment coating was applied were investigated, and in some examples, the appearance, spot weldability after hot stamping, paint adhesion, and paint corrosion resistance after hot stamping were further investigated. The evaluation methods for each evaluation item were as follows.

[0101] (1) Heating rate (Score) The heating rate of each steel plate was calculated from the temperature change obtained from the thermocouple attached to each steel plate and the heating time in the electric heating furnace, and the evaluation was performed. In detail, the heating rate from room temperature to 910°C was calculated, and the evaluation was performed based on the following evaluation criteria. A score of "2" was considered to be a pass. 2: Heating rate of 3.5℃ / s or more 1: Heating rate: 2.0℃ / s or more and less than 3.5℃ / s

[0102] (2) Appearance (Score) Any five points on a 100mm x 100mm test piece were measured according to the Japanese Industrial Standards JIS Z 8781-4(2013) and measure the CIE 1976 L*a*b* color space, and calculate the ratio of the maximum to the minimum L* value (RL* = L* Max / L* value Min ) was evaluated. A score of "2" was considered a pass. 2:1.1 or better 1:1.0 or more and less than 1.1

[0103] (3) Spot weldability after hot stamping The two samples were heated for 6 minutes in an electric heating furnace set at 920°C, and then cooled to room temperature and overlapped. The overlapped parts were spot welded using a DC power source with a pressure of 400 kg and a Cr-Cu electrode with a tip diameter of 6 mm. The current value was increased by 0.5 kA from 7 kA, and the current value 0.5 kA lower than the current value at which two consecutive expulsions occurred was set as the upper limit of the appropriate current range. On the other hand, the welded sample was embedded and the cross section was polished, and the nugget diameter was calculated using the method described in Japanese Industrial Standard JIS Z 3139 (2009), and the current value at which the nugget diameter was 5.5 mm or more was set as the lower limit of the appropriate current range. The evaluation criteria are as follows. A rating of "2" was considered to be acceptable. (Score) 2: The appropriate current range is 1.0kA or more. 1: The appropriate current range is less than 1.0 kA.

[0104] (4) Coating adhesion The sample was subjected to a phosphating conversion treatment and a 15μm thick electrodeposition coating, and then baked at 170℃ for 20 minutes to give a coating film. After that, the sample was immersed in deionized water at 60℃ for 200 hours, and the peeling state of the coating film was checked. A score of "2" was considered to be a pass. (Score) 2: No peeling 1: Some peeling

[0105] (5) Corrosion resistance of coating after hot stamping (4) The coating was scratched with a cutter in the same manner as in (4), and the test was performed according to the method specified in JASO M609 established by the Society of Automotive Engineers of Japan. The width of the coating blister from the scratch after 180 cycles of corrosion testing (maximum value on one side) was measured. A score of "2" was considered a pass. (Score) 2: Bulge width less than 3mm 1: Bulge width 3mm or more

[0106] The evaluation results obtained in Examples 1 to 4 carried out under the above conditions are shown in Tables 2, 3, 4 and 5, respectively.

[0107] <Example 1> In Table 2 below, A1~ A9, A17~ A25 is an example. A10 to A16 are reference examples. a1 to a7 are comparative examples. In this Example 1, when preparing the aqueous treatment liquid, carbon black and at least one of titanium nitride, titanium carbide, titanium oxide, iron oxide, copper oxide, zirconium oxide, silicon nitride, cobalt oxide, and tin oxide were used as compounds other than the binder component. In this Example, the emissivity value at a wavelength of 8.0 μm at 25° C. was adjusted by adjusting the adhesion amount of the surface treatment film.

[0108] In Comparative Example a1, the emissivity at a wavelength of 8.0 μm at 25° C. was as low as 57%, and the heating rate during hot stamping was 2.0° C. / s or more and less than 3.5° C. / s (rating 1). In Comparative Example a2, which did not contain a metal oxide, the emissivity at a wavelength of 8.0 μm at 25° C. was 60%, but because it did not contain a metal oxide, the emissivity at 700° C. was 53%, and the heating rate during hot stamping was 2.0° C. / s or more and less than 3.5° C. / s (rating 1).

[0109] In Comparative Examples a3 and a4, in which the silica content was outside the range of the present invention, the spot weldability after hot stamping was evaluated as "1." In Comparative Examples a5 and a6, in which carbon black and metal oxide were separately formed into films, the L* value ratio was 1.0 or more and less than 1.1, and the appearance was evaluated as 1. In Comparative Example a7, in which the value of the middle part of formula (1) was outside the range of the present invention, the L* value ratio was 1.0 or more and less than 1.1, and the appearance was evaluated as 1.

[0110] On the other hand, invention examples A1~ A9, A17~ A25 , and Reference Examples A10 to A16 The emissivity at a wavelength of 8.0 μm at 25° C. was 60% or more. As a result, the heating rate was 3.5° C. / s or more (rating 2), and the appearance and spot weldability after hot stamping were also rated 2.

[0111] [Table 2]

[0112] <Example 2> In the following examples, the aqueous treatment solution used to form the surface treatment film did not contain silica. The coating adhesion was evaluated while paying attention to the content of carbon black and metal oxide in the surface treatment film. The obtained results are shown in Table 3 below.

[0113] In Table 3, the carbon black (CB) content in the surface treatment film is less than 5% by volume or more than 40% by volume, or the metal oxide content in the surface treatment film is less than 1% by volume or more than 30% by volume. B7, reference example B8, Invention Example In B13 to B15, B20, and B21, peeling occurred in part of the coating film, and the coating adhesion score was 1. On the other hand, in invention examples B2 to B5, in which the carbon black (CB) content in the surface treatment film was 5 to 40 volume % and the metal oxide content in the surface treatment film was 1 to 30 volume %, Reference example B9~B12, Invention ExampleIn B16 to B19, no peeling occurred in the coating film, and the coating film adhesion was rated 2.

[0114] From the above results, it became clear that the coating adhesion can be improved by incorporating 5 to 40% by volume of carbon black and 1 to 30% by volume of metal oxide.

[0115] [Table 3]

[0116] <Example 3> In the following examples, the aqueous treatment liquid used to form the surface treatment film did not contain silica. The heating rate was evaluated while focusing on the ratio of the amount of carbon black and metal oxide attached in the surface treatment film. In this example, the heating rate was evaluated not from room temperature but from 500°C to 910°C. The evaluation criteria were as follows. The results are shown in Table 4 below. (Score) 2: Heating rate of 1.3℃ / s or more 1: Heating rate less than 1.3℃ / s

[0117] In Table 4, the ratio of the amount of carbon black attached to the amount of metal oxide attached is X Oxide / X CB In C1, C7, C8, C14, C15, and C21, where the ratio was less than 0.20 or more than 200.00, the heating rate from 500°C to 910°C was less than 1.3°C / s, and the score was 1. On the other hand, the ratio X Oxide / X CB In C2 to C6, C9 to C13, and C16 to C20, where the average temperature was 0.20 to 200.00, the heating rate from 500°C to 910°C was 1.3°C / s or more, and the score was 2.

[0118] [Table 4]

[0119] <Example 4> In the following examples, the aqueous treatment solution used to form the surface treatment film did not contain silica. The corrosion resistance of the coating film after hot stamping was evaluated, focusing on the amount of carbon black and metal oxide attached in the surface treatment film. The results are shown in Table 5 below.

[0120] In Table 5, the amount of carbon black attached is 0.030 g / m 2 or the amount of metal oxide coating is less than 0.030 g / m 2 Invention example D1, which is less than Reference example D4, Invention Example In D7, the blister width of the coating after hot stamping was 3 mm or more, and the score was 1. On the other hand, the carbon black adhesion amount was 0.030 g / m 2 or more, and the amount of metal oxide attached is 0.030 g / m 2 The above are invention examples D2 and D3, Reference example D5, D6, Invention Example In D8 and D9, the blister width of the coating after hot stamping was less than 3 mm, and the score was 2.

[0121] [Table 5]

[0122] Although the preferred embodiment of the present invention has been described in detail above, the present invention is not limited to such examples. It is clear that a person having ordinary knowledge in the technical field to which the present invention pertains can come up with various modified or amended examples within the scope of the technical ideas described in the claims, and it is understood that these also naturally belong to the technical scope of the present invention.

Claims

1. A surface treatment film having an emissivity of 60% or more at a wavelength of 8.0 μm at 25° C. is provided on the entire surface of at least one surface of the steel sheet, the surface treatment film contains carbon black and one or more oxides selected from the group consisting of Zr oxide and Ti oxide, the carbon black and the oxides being present in a dispersed state throughout the surface treatment film, The surface treatment film has a silica content of 0 to 0.3 g / m 2 and The amount of the carbon black and the amount of the oxide attached are each X CB (g / m 2 ), X Oxide (g / m 2 ) a steel sheet for hot stamping, which satisfies the following formula (1): 118.9≦24280 / {6700 / (100+76×X CB )+18000 / (130+65×X Oxide )}≦332.0 ………… Formula (1)

2. The steel sheet for hot stamping according to claim 1, wherein the surface treatment film contains 5.0 to 40.0 vol. % of the carbon black and 1.0 to 30.0 vol. % of the oxide.

3. The amount of carbon black attached X CB (g / m 2 ) and the amount of oxide attached X Oxide (g / m 2 ) and the ratio X Oxide / X CB The steel sheet for hot stamping according to claim 1 or 2, wherein is 0.20 or more and 200.00 or less.

4. The amount of carbon black attached X CB is 0.030 g / m 2 The amount of oxide adhesion X Oxide is 0.030 g / m 2 The steel sheet for hot stamping according to any one of claims 1 to 3.

5. The steel sheet for hot stamping according to any one of claims 1 to 4, wherein the surface treatment coating has an emissivity at 700 ° C. at a wavelength of 8.0 μm of 60% or more.

6. The steel sheet for hot stamping according to any one of claims 1 to 5, wherein a metal plating layer is provided between a substrate of the steel sheet and the surface treatment film on one or both sides of the steel sheet for hot stamping.

7. A surface treatment film is provided on the entire surface of at least one surface of the steel sheet, The surface treatment film contains one or more oxides selected from the group consisting of Zr oxide and Ti oxide, and the amount of adhesion of the oxide is X Oxide is 0.030 g / m 2 That's all. The surface treatment film has a silica content of 0 to 0.3 g / m 2 A hot stamped component.

Citation Information

Patent Citations

  • Hot press formed product with high corrosion resistance

    JP2003126921A

  • Al PLATED STEEL SHEET FOR HOT PRESS HAVING EXCELLENT TEMPERATURE RISING PROPERTY, AND METHOD FOR PRODUCING THE SAME

    JP2011149084A

  • Method for manufacturing press hardened and coated steel parts at high production rates

    JP2017518438A

Cited By

  • Method for manufacturing welded steel sheets, method for manufacturing tailored blanks, method for manufacturing hot press-formed products, welded steel sheets, tailored blanks, and hot press-formed products

    JP2026166184A